Konsepsi Otonomi Daerah Dalam Pola Relasi Mandala Kedatuan Sriwijaya - Trinanda, Ghea Anissah (Sasdaya: Gadjah Mada Journal of Humanities, 2023)
The Srivijaya Kingdom, in its historical journey, showed a strong commitment to giving more independence to the regions under its control. This meant that these regions could manage their own local matters, taking into account their unique characteristics. This idea played a vital role in boosting the economy and stability of the entire kingdom, making the "kadātuan" system a crucial part of their successful government. The principles of decentralization in Indonesia, based on these historical ideas, have been incorporated into changing laws and regulations, forming a key part of how different areas in Indonesia govern themselves. This paper aims to explore how the concept of local government or decentralization worked in the Srivijaya Kingdom's history. We use a qualitative method that helps us understand complex ideas. By comparing modern decentralization ideas with how the Srivijaya Kingdom managed its decentralization using a "mandala" structure, we see important similarities and connections between the two. The results in this paper show a historical pattern where decentralization were set up and led by a datu. This allowed powers to be shared from the central government to these decentralization regions, which were closely supervised by the central government. This reveals how the idea of decentralization has deep roots in Indonesia's history and is a critical basis for how decentralization works in the country today.